Development of Problems for Higher Order Thinking Skill (HOTS) e-Test on Additive Substance Subject Material - Ina Wulandari; Hairida Hairida; Rahmat Rasmawan; Eny Enawati; Rini Muharini (Hydrogen: Jurnal Kependidikan Kimia, 2023)
Indonesia is one of the countries with low PISA (Program for International Students Assessment) achievement levels based on survey results due to the low level of higher order thinking skill of students. The causes of the low level of higher order thinking of students in Indonesia include the question given have not met the criteria of HOTS questions and the lack of ability of educations in making Higher Order Thinking Skill (HOTS) questions. This study was conducted to determine the feasibility of HOTS e-questions. The aim of developing higher-order thinking Skill (HOTS) questions in electronic form in the conditions of transition from pandemic to endemic now is so that they are easily accessible to students anywhere and at any time. The method used in this research is research and development (R&D) with ADDIE model which has 4 stages, namely: Analysis; at this stage, needs analysis and performance analysis are carried out, Design; at this stage, the process of designing or creating learning tools occurs, Development; at this stage, learning tools are developed and validated from previously selected learning sources, Implementation, and Evaluation. The form of questions that have been developed consists of multiple choice and eesay questions and scring guidelines. The overall validation results of the HOTS e-questions amounted to 94.47% with very feasible criteria. Based on the validation results, HOTS e-questions on additive are suitable for use in learning activities and are tested during science subjects at school.